Castle (Erdödy) Kerestinec - Galić, Marin; Milaković, Saša (Program održivog razvoja Svete Nedelje, Jastrebarskog i Samobora, 2024)
This paper provides a historical and architectural overview of the Erdödy Castle in Kerestinec based on field research and historical methods that gathered data and archival information. In the analytical-experimental section, a more in-depth external and internal analysis is conducted through PEST and SWOT analyses, highlighting potential 'forces' impacting the Erdödy Castle. It was also necessary to analyse current social and technological trends. One of the identified target groups includes people associated with the Rimac Campus, though other target groups are also mentioned, and buyer personas were developed based on these. Several solutions are proposed for filling the castle with content, all integrated under the working theme "Sound of Kerestinec." The theme focuses on the sense of hearing, though visual and gastronomic solutions and high-level technology complement the concept. Due to a music school being one of the potential and realistic solutions, other complementary solutions are also proposed, such as a vinyl shop, presentation rooms, and a restaurant, all aligning with the "Sound of Kerestinec" theme. With this offering, the castle could become a 'global embassy' that connects, celebrates, and promotes world cultures and traditions, focusing on music and visual arts.